(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article analyzes the content of the modern educational strategy, the theoretical and methodological foundations of the use of innovative educational technologies in it, and their role in increasing the efficiency of the educational process. The impact of innovative technologies on the quality of education, their contribution to the formation of student and teacher competencies are based on this.